Determination of BCG vaccination with PPD test and tuberculosis infection prevalence among primary school children in Elazig - Sen, C.; Aygun, A.D.; Altunisik, E.; Kocabay, K. (My University, 1998)
BCG immunization and tuberculin response were evaluated in 2,076 healthy primary school students in Elazig who were six to 13 years old (mean ± SD, 9.4±2.02 years). While 261 (12.6%) children had two and 1,364 (65.7%) had at least one BCG scar, 451 (21.7%) children had no scar. The mean measured tuberculin responses of 451 BCG-negative children was 2.4±3.4 mm with a 95th percentile value of 10 mm. Of the children who had one or two scars, mean measured tuberculin responses were 5.8±4.9 mm and 11.0±3.9 mm, and the 95th percentile values were 14 mm and 16 mm, respectively. A significant statistical difference was found between the three groups (p<0.001). Children with tuberculin reactions greater than 95th percentile were accepted as infected and were referred to the local tuberculous control center where further examination and investigations were done. No active tuberculosis was found in tuberculin positive cases. Infection prevalence was 1.11 percent. The annual infection rate was 20.2 percent for the seven years age of group, and 12.3 percent for the twelve years of age group in BCG scar-negative children.
Elazig il merkezindeki ilkogretim okulu cocuklarinda PPD ile BCG asisinin degerlendirilmesi ve tuberkuloz enfeksiyon prevalansi
Keywords: BCG; Infection rate; PPD reaction; Prevalence; Tuberculosis